A Revised Checklist of the UK Silverfish (Zygentoma: Lepismatidae) - Chick, Andrew I. R. (Zootaxa, 2018)
With the discovery of Ctenolepisma longicaudata by Goddard et al. (2016) and the record of Ctenolepisma lineata as a possible introduced pest by Notton (2018), as well as the changes to the higher classification reported by Barnard (2011), the current number of UK Lepismatidae (silverfish and firebrats) that an entomologist might encounter has doubled. Therefore, the most recent checklist (Kloet & Hicks 1964) is in need of revision. This paper aims to provide an updated check list, guide to keys that can be used to Identify UK Lepismatidae as well as to provide an overview of UK species.